Natural Polyketides Isolated from the Endophytic Fungus Phomopsis sp. CAM212 with a Semisynthetic Derivative Downregulating the ERK/IκBα Signaling Pathways - Jouda, Jean-Bosco; Njoya, Emmanuel Mfotie; Fobofou, Serge Alain Tanemossu; Zhou, Zong Yuan; Qiang, Zhe; Mbazoa, Céline Djama; Brandt, Wolfgang; Zhang, Guo-lin; Wandji, Jean; Wang, Fei (Planta Medica, 2020)
Three previously undescribed natural products, phomopsinin A – C (1 – 3), together with three known compounds, namely, cis-hydroxymellein (4), phomoxanthone A (5) and cytochalasin L-696,474 (6), were isolated from the solid culture of Phomopsis sp. CAM212, an endophytic fungus obtained from Garcinia xanthochymus. Their structures were determined on the basis of spectroscopic data, including IR, NMR, and MS. The absolute configurations of 1 and 2 were assigned by comparing their experimental and calculated ECD spectra. Acetylation of compound 1 yielded 1a, a new natural product derivative that was tested together with other isolated compounds on lipopolysaccharide-stimulated RAW 264.7 cells. Cytochalasin L-696,474 (6) was found to significantly inhibit nitric oxide production, but was highly cytotoxic to the treated cells, whereas compound 1 slightly inhibited nitric oxide production, which was not significantly different compared to lipopolysaccharide-treated cells. Remarkably, the acetylated derivative of 1, compound 1a, significantly inhibited nitric oxide production with an IC50 value of 14.8 µM and no cytotoxic effect on treated cells, thereby showing the importance of the acetyl group in the anti-inflammatory activity of 1a. The study of the mechanism of action revealed that 1a decreases the expression of inducible nitric oxide synthase, cyclooxygenase 2, and proinflammatory cytokine IL-6 without an effect on IL-1β expression. Moreover, it was found that 1a exerts its anti-inflammatory activity in lipopolysaccharide-stimulated RAW 264.7 macrophage cells by downregulating the activation of ERK1/2 and by preventing the translocation of nuclear factor κB. Thus, derivatives of phomopsinin A (1), such as compound 1a, could provide new anti-inflammatory leads.
Keywords: Garcinia xanthochymus; Phomopsis sp.; polyketides; phomopsinin; anti-inflammatory; cytokines; MAPKs; NF-κB